2010
DOI: 10.1111/j.1600-0560.2010.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

CD10, p63 and CD99 expression in the differential diagnosis of atypical fibroxanthoma, spindle cell squamous cell carcinoma and desmoplastic melanoma

Abstract: CD10 positivity is relatively specific in this context for the diagnosis of AFX. Its utility is enhanced when only strong, diffuse membranocytoplasmic staining is considered as a positive result. In contrast to prior reports, p63 was not found to be highly sensitive for SCC. Similarly, CD99 showed no preferential staining of any single diagnostic group of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
2
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 33 publications
(54 reference statements)
2
93
2
11
Order By: Relevance
“…QPCR analysis, which displays increased sensitivity for detecting low expression levels of isoforms, dem onstrated infrequent expression of TP63 isoforms in primary human melanocyte cultures but significantly elevated expres sion in >70% of established melanoma cell lines. In contrast with previous immunohistochemistry studies, which showed little or no expression of p63 protein (Brinck et al, 2002;Di Como et al, 2002;ReisFilho et al, 2003b;Dotto and Glusac, 2006;Bourne et al, 2008;Morgan et al, 2008;Sakiz et al, 2009;Kanner et al, 2010), our data provide the first evi dence of marked upregulation of both p63 mRNA and pro tein in melanoma cell lines.…”
Section: Depletion Of P63 Sensitizes Melanoma Cells To a Mitochondriacontrasting
confidence: 54%
See 1 more Smart Citation
“…QPCR analysis, which displays increased sensitivity for detecting low expression levels of isoforms, dem onstrated infrequent expression of TP63 isoforms in primary human melanocyte cultures but significantly elevated expres sion in >70% of established melanoma cell lines. In contrast with previous immunohistochemistry studies, which showed little or no expression of p63 protein (Brinck et al, 2002;Di Como et al, 2002;ReisFilho et al, 2003b;Dotto and Glusac, 2006;Bourne et al, 2008;Morgan et al, 2008;Sakiz et al, 2009;Kanner et al, 2010), our data provide the first evi dence of marked upregulation of both p63 mRNA and pro tein in melanoma cell lines.…”
Section: Depletion Of P63 Sensitizes Melanoma Cells To a Mitochondriacontrasting
confidence: 54%
“…Whole genome array studies have demonstrated 1/20 (5%) desmoplastic melanomas (Kanner et al, 2010). Expression of TAp63 and Np63 in uveal melanoma was dem onstrated in 12/18 (66.7%) and 1/18 (5.6%) cell lines, respec tively (Kilic et al, 2008).…”
mentioning
confidence: 99%
“…69,86 Studies have shown that CD163 is more specific for histiocytes than is CD68, which is an organelle-specific marker that stains lysosomes. Because CD68 reactivity is seen in some AFXs, it is not surprising that CD163 expression was reported 87 ; however, further studies were unable to replicate those results.…”
Section: Atypical Fibroxanthomamentioning
confidence: 99%
“…However, p63 is not entirely specific and shows focal labeling in rare cases of AFX and leiomyosarcoma. [67][68][69] As part of an IHC panel, p63 can be helpful in the differential diagnosis of spindle cell neoplasms (Table 3). 67 …”
Section: Spindle Cell Sccmentioning
confidence: 99%
See 1 more Smart Citation